2020
DOI: 10.3390/antibiotics9080458
|View full text |Cite
|
Sign up to set email alerts
|

Post-Antibiotic Effect of Ampicillin and Levofloxacin to Escherichia coli and Staphylococcus aureus Based on Microscopic Imaging Analysis

Abstract: Post-antibiotic effect (PAE) is the continued suppression of bacterial growth following a limited exposure to an antimicrobial agent. The presence of PAE needs consequential consideration in designing antibiotic dosage regimens. To understand the behavior of bacteria, PAE provides information on how long antibiotics are applied to the bacteria. Conventional methods of measuring PAE depend on population detection and have limitations for understanding the individual behavior of bacteria. To observe the PAE, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…, persistence of the antimicrobial effect after brief exposure to an antimicrobial agent. 36 Thus, it was tentatively concluded that PAE aggravated BT after losing the interference of DKGM and KOGM.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…, persistence of the antimicrobial effect after brief exposure to an antimicrobial agent. 36 Thus, it was tentatively concluded that PAE aggravated BT after losing the interference of DKGM and KOGM.…”
Section: Resultsmentioning
confidence: 97%
“…This is possibly because most of the antibiotics, including the antibiotics used in this study, possessed a postantibiotic effect (PAE), i.e., persistence of the antimicrobial effect after brief exposure to an antimicrobial agent. 36 Thus, it was tentatively concluded that PAE aggravated BT after losing the interference of DKGM and KOGM. As depicted in Table 2, except in the KK group, the translocated bacteria numbers in other groups were not significantly different than those in the AN group, and the numbers for the…”
Section: Food and Function Papermentioning
confidence: 97%
“…Aliquots from each tube were pooled out at hourly time intervals and plated on nutrient agar plates to estimate CFU per mL. The PAE was calculated using the equation PAE = T – C , where T is the time required for the antibiotic-exposed culture to increase by 1 log 10 CFU per mL, and C is the corresponding time taken by the untreated control . Three independent experiments were done to obtain the average data.…”
Section: Methodsmentioning
confidence: 99%
“…Although MAC may guide antibiotic dosing, post-antibiotics effects are relatively short lived. In linezolid and ampicillin, the inhibition lasted between 1-3 h, depending on the type of bacteria treated [53,54]. For quinolones, the said effect may persist for up to 6 h [54].…”
Section: Pharmacokinetics and Pharmacodynamics Of Antibioticsmentioning
confidence: 99%
“…In linezolid and ampicillin, the inhibition lasted between 1-3 h, depending on the type of bacteria treated [53,54]. For quinolones, the said effect may persist for up to 6 h [54]. Mechanisms are myriad and include inflicting sublethal damage, the persistence of antibiotics in periplasmic space, or efflux inhibition [55][56][57].…”
Section: Pharmacokinetics and Pharmacodynamics Of Antibioticsmentioning
confidence: 99%